Comparative study of the poisoning effect of NaCl and Na2O on selective catalytic reduction of NO with NH3 over V2O5-WO3/TiO2 catalyst. Issue 4 (August 2019) - Tian, Yuanmeng; Yang, Jian; Yang, Chen; Lin, Fan; Hu, Guang; Kong, Ming; Liu, Qingcai
Abstract: V2 O5 -WO3 /TiO2 catalyst has been widely used in industry. Alkali metals would cause the deactivation of V2 O5 -WO3 /TiO2 catalyst. In this paper, the poisoning deactivation of NaCl and Na2 O on V2 O5 -WO3 /TiO2 catalyst was compared. The properties of the catalysts were characterized by BET, XPS, H2 -TPR, NH3 -TPD and in situ DRIFTS. It was found the addition of NaCl, Na2 O affected the structure, redox properties and acid sites of V2 O5 -WO3 /TiO2 catalyst. Na + would react with VOH to form VONa + destroying the structure of Brønsted sites and affect the adsorption of NH3 on the Lewis acid to restrain the generation of V 4+ NH2 to decrease the SCR activity, occupying the oxygen vacancy made a decline in chemisorbed oxygen. The poisoning effect of NaCl was stronger than that of Na2 O, even if the property of weak-chemisorption of NaCl is stronger and possessed more V 5+ species. There is a reason that NaCl provided HCl and then reacted with VO2 to form ClVOClOH to adsorb NH3 . However, ClVOClOH cannot make the catalysis selectively generate nitrogen and water. Graphical abstract: Image 1 Highlights: The poisoning effect of NaCl is more serious than that of Na2 O, even if NaCl doped V2 O5 -WO3 /TiO2 catalyst possess more V 5+ and surface acidity. There is a weak NH3 adsorption site VO(OH) (Cl)2 on NaCl poisoned catalyst surface. VO(OH)(Cl)2 cannot selectively generate nitrogen and water.